PERAN ANALISIS PASAR, SEGMENTASI, DAN PENETAPAN POSISI MEREK DALAM MERANCANG STRATEGI PEMASARAN YANG EFEKTIF UNTUK MEMENUHI KEBUTUHAN DAN PREFERENSI KONSUMEN DI ERA PERSAINGAN GLOBAL - Al-Amin; Taufik Udango (JIEKA: Jurnal Integrasi Ekonomi, Keuangan, dan Akuntansi, 2025)
This study examines the integral role of market analysis, market segmentation, and brand positioning in designing effective marketing strategies to meet consumer needs and preferences in an era of global competition characterised by digital disruption and cultural heterogeneity. Through a literature review method, the study found that market analysis—using the PESTEL, Porter's Five Forces, and big data AI-based SWOT frameworks—serves as a predictive foundation for identifying opportunities in emerging Southeast Asian markets such as Indonesia, with an e-commerce CAGR of 25%. while the integration of demographic-geographic-psychographic-behavioural segmentation with brand positioning, such as Unilever sachets or Patagonia eco-activists, increases campaign relevance by up to 50%, brand loyalty, and ROI through glocalisation and hyper-personalisation. The conclusion emphasises that the synergy of these three elements is essential for local companies to compete globally by 2025, with recommendations for implementing NVivo for thematic analysis and an adaptive STP framework to adapt to AR-social commerce trends.